Fen meadows on the move for the conservation of Maculinea (Phengaris) teleius butterflies - Wynhoff, I.; Kolvoort, A. M.; Bassignana, C. F.; Berg, M. P.; Van Langevelde, F. (Journal of insect conservation, 2017)
In the Netherlands, a single population of the obligate myrmecophilic butterfly Maculinea (Phengaris) teleius has survived on only 3 ha of habitat for more than 25 years, whereas at least 40 ha of habitat are thought to be required for a sustainable metapopulation. Therefore, 170 ha of farmland is being restored to wet meadows within a LIFE + project by large-scale soil excavation and hay inoculation. For successful restoration, the habitat requirements of the butterfly, with Sanguisorba officinalis as host plant and its particular life cycle as parasite of the ant species Myrmica scabrinodis , have to be taken into account. We tested whether colonization of nests of this ant species in the restoration areas is facilitated by translocation of sods collected from fen meadows. We divided 54 sods, each sized 1 m 2 , randomly over six patches and measured vegetation development and ant presence in the sods and surrounding control plots for 2 years. In the first summer, significantly more Myrmica ants were found in the transplanted sods in comparison to the surrounding area. Herb cover had a significant positive effect on Myrmica ant presence while it did not affect the presence of the pioneer ant species Lasius niger . In the second year, Myrmica ants were found in the surrounding control plots as well. This study contributes to the knowledge-base required for the design of restoration projects aimed at expanding the habitat of the critically endangered butterfly Maculinea (Phengaris) teleius .